(untitled) (Research, Society and Development, 2021)
This study aimed to understand the role of the school psychologist in the inclusion of atypical children. Data were collected through a seeding interview conducted with a psychologist from the Association of Friends of Autistic people of Piauí (AMA). The answers of the interview were categorized into three categories: the conception of atypical development and school inclusion, the attribution of school psychology and the contribution of the school psychologist to the school inclusion of atypical children. The results showed that atypical development can be understood as a development pattern that is not considered normative for the age group of the individual, making it necessary to have a well-elaborated inclusion project in the educational institution. It is up to the school psychologist to work together with the school network, the students’ families and the community, offering support and guidance, aiming to make the school an environment that provides for equal development.